User centric cloud service model in public sectors: Policy implications of cloud services - Dong-Hee Shin; Hongseok Yoon; Jaegil Lee; Yohan Moon; Namchul Kim; Hoyeon Cho (International Telecommunications Society (ITS), 2014)
This study examines the acceptance of cloud computing services in government agencies by focusing on the key characteristics that affect behavioral intent. The study expanded upon the technology acceptance model by incorporating contextual factors such as availability, access, security, and reliability. The research model was empirically verified by investigating the perception of users working in public institutions. Modeling results showed that user intentions and behaviors were largely influenced by the perceived features of cloud services. Also these features were found to be the significant antecedents of cloud computing usefulness and ease of use. The findings should guide governments' promotion of cloud public services to increase user awareness by enhancing usability and appeal and ensuring security.
Keywords: 330; Cloud computing; cloud services; cloud policy; public sector; technology acceptance model; security; reliability; access